2020
DOI: 10.1051/matecconf/202030500090
|View full text |Cite
|
Sign up to set email alerts
|

Water reuse as a secure pathway to deal with water scarcity

Abstract: An adequate access to water supply systems is crucial for a sustainable future. Climate change is expected to increase water shortage problems worldwide. Reuse/recycling of treated wastewater for domestic and/or agricultural purposes can be considered an interesting water supply: it is independent from seasonal drought and meteorological variability and able to cover the peak of water demand. In the case of direct reuse, the parameter of treated water must comply with the reuse limits for biological oxygen dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In the treatment of contaminated water, the composite membranes demonstrated sustained antibacterial activity and good reusability. This study highlights the importance of investigating materials that show antibacterial activity, which is a very important topic in water treatment, especially with emphasis when water reuse is aimed [14].…”
Section: Resultsmentioning
confidence: 97%
“…In the treatment of contaminated water, the composite membranes demonstrated sustained antibacterial activity and good reusability. This study highlights the importance of investigating materials that show antibacterial activity, which is a very important topic in water treatment, especially with emphasis when water reuse is aimed [14].…”
Section: Resultsmentioning
confidence: 97%
“…International observations already indicate that approximately 1/10 of the population lacks access to basic drinking water services. With the global population increasing and a lack of initiatives to address the crisis of available water resources, it is evident that the number of people deprived of the fundamental right to water will rise substantially in the upcoming years [6]. This statement is also supported by Figure 1, where it is indicated that the number of urban citizens who encounter water shortage-seasonal or longterm-will continue to increase [7].…”
Section: The Impacts Of Reckless Water Consumptionmentioning
confidence: 83%
“…Furthermore, periodic environmental stress, including drought, is predicted to increase water scarcity problems worldwide. This creates additional and serious functional limitations for plant growth and also has significant adverse influences on crop yields [2,3]. Sand dune plants play an important role in dune stabilization and protect the adjacent coastal beaches from wind and water erosion but they are subjected to severe environmental stresses such as drought [4,5].…”
Section: Introductionmentioning
confidence: 99%